Optimizing performance with a 1-minute high-intensity re-warm up protocol in basketball substitutes - Koutsouridis, C.; Galazoulas, C.; Manou, V.; Stavropoulos, N.; Prantsidis, D. I. (Journal of Human Sport & Exercise, 2025)
The aim of the study was to investigate whether a 1-minute high-intensity Re-Warm Up (RWU) protocol on a cycle ergometer could attenuate the negative effects of passive rest on basketball players' performance. Twelve semi-professional players completed two trials on consecutive days in a counterbalanced, randomized design with repeated measures. Following a structured warm-up (WU), the trials included: a) 15 minutes of passive rest (CON) and b) 13 minutes of passive rest, followed by 1 minute of cycling at 80% VO2max and 1 minute of rest (RWU80). Post-WU and post-RWU measurements included countermovement jump (CMJ), modified agility t-test (MAT), heart rate (HR), body temperature (BT), rating of perceived exertion (RPE), and perceived readiness rating (PRR). CON group showed significant decreases in all variables, while RWU80 attenuated these losses in HR (p = .127), RPE (p = .058) and PRR (p = .236). Between the two post-RWU measurements, the RWU80 showed significantly improved results in MAT (p = .05) and HR (p < .001) and higher RPE (p = .002). Although statistically significant differences did not appear in all variables, the RWU80 led to greater readiness of the substitute players to enter the game com-pared to the 15 minutes of passive rest.